Training in infection prevention and control: survey on the volume and on the learning demands of healthcare-associated infections control figures in the Emilia-Romagna Region (Northern Italy) - Ferrari, Eleonora; Scannavini, Patrizia; Palandri, Lucia; Fabbri, Elisa; Tura, Grazia; Bedosti, Catia; Zanni, Angela; Mosci, Daniela; Righi, Elena; Vecchi, Elena (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. In the context of Infections Prevention and Control activities, the training of healthcare-associated infection control figures is crucial; the COVID-19 pandemic further emphasized the necessity of ensuring a widespread and stable level of skills over time for such professionals. The present work aims to identify the number and training needs of the personnel working in the Emilia-Romagna Region’s healthcare facilities as “healthcare-associated infection control figures”. Methods. Data were collected through a survey created by experts from the Regional Group “Training in the prevention and control of antibiotic resistance”. The questionnaire explored the number, professional and educational background, and training requirements of Healthcare-associated infections control figures in Emilia-Romagna. Results. With 73 figures dedicated to Healthcare-associated infections control, the Emilia-Romagna Region appears to be in line with the European standard ratio (1 professional every 125 beds). Professionals with a nursing background, over 50 years old and of female sex prevail in the group, while the training needs expressed include both theoretical and practical aspects. Conclusions. Healthcare assistants and nursing staff represent a fundamental resource for the implementation of infection preven- tion and control programs in our healthcare facilities; continuous, multidisciplinary and targeted training of these professionals is confirmed as necessary.